Transformational Leadership Skills among Public Elementary School Administrators - Susan Poliden (Philippine Association of Institutions for Research, Inc., 2019)
This study investigated the transformational leadership skills and leadership styles of the public elementary school administrators in Bokod District, Bokod, Benguet. Data gathered were summarized, analyzed and cross-tabulated. Descriptive statistics like weighted mean, percentages and ranks were computed from test results. Responses from the respondents were also classified according to the number of years as an administrator and the kind of designation whether a) Principal, b) Head Teacher, c) Teacher-in-Charge. Analysis for transformational leadership survey measured leadership skills on six factors: Charisma, Social, Vision, Transactional, Delegation, and Execution while analysis for the leadership style survey determined the leadership styles of the respondents whether they are authoritarian, democratic or laissez-faire. The public elementary school administrators of Bokod District have generally varied transformational leadership skills and leadership styles. The leadership styles practiced by the respondents regardless of the number of years as administrators and the kind of designations are Democratic followed by Laissez-faire and last, Authoritarian style of leadership. It is recommended that Charisma as transformational leadership skill be revisited and be strengthened by the school administrators, and the interplay of the different leadership styles is paramount in school management. Hence, the principals, head teachers and teachers-in-charge need to be flexible in their management at all times.